2001
DOI: 10.1515/znc-2001-9-1040
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Mg2+- ATPase Activity in the Hypoglycemic Adult Rat Brain

Abstract: The effects of different a-D-Glucose (Glu) concentrations (0 -16 mᴍ) on Na+, K+-ATPase and Mg2+-ATPase activities were investigated in homogenates of adult male rat whole brain at 37 °C. The enzyme activities were determined after 1h preincubation with Glu. Brain Na+, K+-ATPase was not affected by Glu different concentrations. On the contrary, Mg2+-ATPase activity was considerably reduced with Glu concentrations lower than 4 mᴍ. The enzyme was inhibited 40%, 50% or 80% with 3, 2 or 1 mᴍ of Glu, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In particular, it was shown that EGTA (EDTA) and Ca 2+ can modify the neuronal membrane Na + , K + -ATPase [19] [20]. At the same time, there was observed a change in the activity of both transport P-type ATPases and "total" Mg 2+ -ATPase or "basal" Mg 2+ -ATPase that are insensitive to ouabain [21] [22]. Therefore, we investigated the effect of Ca 2+ on the "basal" and Cl − , "basal" Mg 2+ -ATPase decreased to 55% and amounted to 4.4 µmol P i /h/mg protein.…”
Section: Hco − -Atpase Activitymentioning
confidence: 98%
“…In particular, it was shown that EGTA (EDTA) and Ca 2+ can modify the neuronal membrane Na + , K + -ATPase [19] [20]. At the same time, there was observed a change in the activity of both transport P-type ATPases and "total" Mg 2+ -ATPase or "basal" Mg 2+ -ATPase that are insensitive to ouabain [21] [22]. Therefore, we investigated the effect of Ca 2+ on the "basal" and Cl − , "basal" Mg 2+ -ATPase decreased to 55% and amounted to 4.4 µmol P i /h/mg protein.…”
Section: Hco − -Atpase Activitymentioning
confidence: 98%